EXTH-33. PRIMING OF SYNNOTCH CAR T CELLS VIA CNS-SPECIFIC ANTIGEN ALLOWS SPATIAL AND TEMPORAL REGULATION OF CAR EXPRESSION, EFFECTIVE HOMING AND PERSISTENCE OF T CELLS IN THE CNS. (14th November 2022) - Watchmaker, Payal; Simic, Milos; Diebold, David; Pineo-Cavanaugh, Psalm; Deucker, Jason; Yu, Wei; Lim, Wendell; Okada, Hideho
Abstract: One of the key challenges in the development of CAR-T therapy is the absence of target antigens that are tumor-specific and have homogenous expression. To safely target glioblastoma-associated antigens (GAAs) in the tumor without attacking normal tissue expressing the same GAAs outside of the brain, we adapted a novel synthetic Notch (synNotch) receptor system and established a "prime and kill" sequential two-receptor CAR circuit. We used glioblastoma- (GBM) specific neoantigen EGFRvIII as a priming signal for synNotch receptor and have reported robust antitumor response in the mice bearing intracerebral PDX tumor with heterogenous EGFRvIII expression. However, less than 20% of adult GBM cases express EGFRvIII. Furthermore, EGFRvIII expression can diminish over time even after its detection in the primary GBM, and the EGFRvIII-synNotch primed CAR T cells may deplete EGFRvIII-expressing GBM cells via their cytotoxic effects, thereby losing the priming signal. To overcome these inherent challenges of the EGFRvIII-priming strategy, we used CNS tissue-specific antigens as priming signal to drive localized expression of the CAR against EphA2 and IL-13Rα2 and bypassed the need for tumor-specific antigen. We have found BCAN (also known as Brevican) as the most promising priming antigen among several CNS-specific cell surface proteins that we evaluated. When mice bearing intracerebral GBM6 PDX received a single IV infusion of T cells engineered with the α-BCANsynNotch- > α-EphA2/IL-13Rα2 CAR (B-SYNC) circuit, all mice (10/10) demonstrated complete regression of the tumor. Furthermore, these B-SYNC T cells were significantly more efficacious than constitutively expressed EphA2/IL-13Rα2 CAR T cells, associated with superior persistence and less exhausted phenotype. Thus, the B-SYNC approach represents a conceptual novelty of CNS tissue-specific CAR activation. This also enhances the translational significance of synNotch-CAR T cells by widely extending the eligibility to EGFRvIII-negative glioma patients. We will develop and conduct a phase I study to evaluate our hypothesis.